Failure mode maps of bio-inspired sandwich beams under repeated low-velocity impact - Abo Sabah, S.H.; Kueh, A.B.H.; Muhamad Bunnori, Norazura (Elsevier, 2019)
Existing sandwich structures failure maps are confined only to data from the quasi-static bending tests even for describing failure modes due to the impact event. Strengths of the constituent layers, which are not well-described by these maps, can reasonably change especially under the repeated impact load case. Hence, a new series of more realistic failure mode maps have been developed from the experimentally and numerically obtained observations on recently proposed bio-inspired dual-core sandwich beams in the presence of repeated low-velocity impacts of different energy levels. The beams consist of top and bottom carbon fiber reinforced polymer skins sandwiching the rubber and aluminum honeycomb cores. Departing from the modified Gibson model, an actual presentation of skin and core behaviors has been modeled following the trend of strengths variations for the construction of the failure mode maps when subjected to numerous impact numbers and energies. The produced maps offer the flexibility to accommodate the changes in strengths due to deterioration or densification of constituent layers after impact, and hence following more favorably the physical failure description of the sandwich beams. Accompanying these maps, a general set of mathematical expressions have also been produced for practical convenience. It is found that the failures from observations are within the proposed map boundaries with accuracies ranging from 85.7% to 100%. © 2019 Elsevier Ltd